The The impact of materiality and stakeholder engagement on firm sustainability reporting - Salsabilla, Shafira; Saraswati, Erwin; Andayani, Wuryan (Journal of Innovation in Business and Economics, 2024)
This paper empirically examines the influence of materiality and stakeholder engagement on the quality of sustainability reports in manufacturing companies in Indonesia from 2017 to 2022. The quality of sustainability reporting is measured using four index dimensions: relative quantity of disclosure, density, accuracy, and management orientation. Materiality and stakeholder engagement are assessed using a content analysis methodology, with relevance of disclosure as the measurement criterion. The regression analysis reveals that materiality has a significant negative effect on the quality of sustainability reporting. Conversely, stakeholder engagement has a significant positive effect on the quality of sustainability reporting. These findings highlight a potential trade-off: an excessive emphasis on materiality may lead to the omission of other critical components, thereby reducing the overall quality and comprehensiveness of sustainability reporting.